2010
DOI: 10.5424/sjar/2010081-1160
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of some infiltration models and hydraulic parameters

Abstract: The evaluation of infiltration characteristics and some parameters of infiltration models such as sorptivity and final steady infiltration rate in soils are important in agriculture. The aim of this study was to evaluate some of the most common models used to estimate final soil infiltration rate. The equality of final infiltration rate with saturated hydraulic conductivity (K s ) was also tested. Moreover, values of the estimated sorptivity from the Philip's model were compared to estimates by selected pedotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 26 publications
3
43
0
3
Order By: Relevance
“…Also, Osuji et al (2010) reported significant relationships between steady infiltration rates and soil organic matter, bulk density, and total porosity. Shukla et al (2003), Bormann and Klassen (2008) and Haghighi et al (2010) attributed changes in infiltration rates to soil hydraulic properties, porosity, soil organic matter and bulk density and different land use practices.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Osuji et al (2010) reported significant relationships between steady infiltration rates and soil organic matter, bulk density, and total porosity. Shukla et al (2003), Bormann and Klassen (2008) and Haghighi et al (2010) attributed changes in infiltration rates to soil hydraulic properties, porosity, soil organic matter and bulk density and different land use practices.…”
Section: Introductionmentioning
confidence: 99%
“…Deep and Das (2008) used various optimization techniques to estimate infiltration model parameters that included Software Language of Interactive General Optimization (LINGO), Binary Genetic algorithm (BGA), Random Search Technique (RST), Hybrid Binary Genetic Algorithm (HBGA), Real coded Genetic Algorithm using Laplace crossover and Power Mutation (LX-PM), and its hybrid version (H-LX-PM) thereby reporting HBGA as best suited optimization technique for estimation of infiltration rates. Haghighi et al (2010) used MATLAB for estimation of final infiltration and sorptivity factor for Taleghan watershed in Iran and concluded that use of pedotransfer functions (PTFs) is limited to specific similar sites for which they are calibrated. GENSTAT a statistical software was employed by Ogbe et al (2011) to fit infiltration equations to Nigerian soils.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, these attributes showed an inverse correlation with Bd, which indicates that the water flow in the soil is restricted by the high values of Bd. It can be observed that the process of infiltration is weakly influenced by the sand and clay contents (Haghighi et al, 2010), as is confirmed by the low values of coefficients of correlation between those attributes with respect to Ci, Bi, S 1 , and Ks, possibly explained by the native savannah condition of the soil and the lower variability that sand and clay content. In the same way, a direct relationship between clay and Sm can be observed, and an inverse one between sand and Sm, which indicates that a high clay content, greater soil moisture, and thus the greater capacity for water storage.…”
Section: Resultsmentioning
confidence: 61%